MAN IN POWER RELATIONS BY M. FOUCAULT - Федоровская, О. Б. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted the questions of co-operation of power and individual in works of francuzkogo philosopher Mishelya Foucault. The evolution of his looks is examined in the article, the analysis of concepts «power-knowledge» and «power-word» is given.